2018
DOI: 10.1001/jamainternmed.2018.2562
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Bundled Hospital-at-Home and 30-Day Postacute Transitional Care Program With Clinical Outcomes and Patient Experiences

Abstract: IMPORTANCE Hospital-at-home (HaH) care provides acute hospital-level care in a patient's home as a substitute for traditional inpatient care. In September 2017, the Physician-Focused Payment Model Technical Advisory Committee recommended implementation of an alternative payment model for a new model of HaH that bundles the acute episode with 30 days of postacute transitional care. OBJECTIVE To report outcomes of this new payment model for HaH care. DESIGN, SETTING, AND PARTICIPANTS Case-control study of HaH ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 24 publications
6
191
1
1
Order By: Relevance
“…These services might be more frequent follow-up, targeted exercise programs, multidisciplinary outpatient chronic disease management, or in-home services, as has been shown to be effective in individuals with other disabling conditions. (19)(20)(21)(22) Furthermore, the Food and Drug Administration emphasizes patient-focused drug development for selecting outcomes in interventional trials. They recommend including measures of how a patient "feels or functions."…”
mentioning
confidence: 99%
“…These services might be more frequent follow-up, targeted exercise programs, multidisciplinary outpatient chronic disease management, or in-home services, as has been shown to be effective in individuals with other disabling conditions. (19)(20)(21)(22) Furthermore, the Food and Drug Administration emphasizes patient-focused drug development for selecting outcomes in interventional trials. They recommend including measures of how a patient "feels or functions."…”
mentioning
confidence: 99%
“…Recent reports in the media and through personal contact with the HaH‐Plus team demonstrate that health systems are increasingly implementing HaH programs and entering into risk contracts with insurers. This shows the potential viability and demand of this model of care as the US healthcare system moves increasingly toward value‐based care, and the outcomes of this trial add impetus due to the high quality, high satisfaction, and significant cost savings found …”
Section: Discussionmentioning
confidence: 95%
“…HaH‐Plus began enrolling patients in the fall of 2014. Described elsewhere, HaH‐Plus was found to reduce lengths of stay, lower readmissions and emergency department (ED) visits, and increase satisfaction . The aim of this study was to examine facilitators and barriers to implementation of HaH‐Plus over its first year of operation to provide others the opportunity to plan effectively for operationalization.…”
Section: Introductionmentioning
confidence: 99%
“…In this US-based case–control study, Federman and colleagues6 found that hospital-at-home care bundled with a 30-day postacute transitional care programme was associated with improved patient outcomes and experience. Patients presenting to either of two affiliated academic medical centres in New York were considered eligible for hospital-at-home admission if they were more than 18 years old, had fee-for-service Medicare or coverage from a single private insurer that contracted with the facility, and required inpatient admission.…”
Section: Association Of a Bundled Hospital-at-home And 30-day Postacumentioning
confidence: 97%